Changes in stiffness of the specific regions of knee extensor mechanism after static stretching - Zhu, Yuanchun; Feng, Yanan; Huang, Fangchao; Li, Yapeng; Wang, Wenjing; Wang, Xueqiang; Cao, Xiangyang; Zhang, Zhijie (Frontiers in Bioengineering and Biotechnology, 2022)
Decreased muscle stiffness could reduce musculotendinous injury risk in sports and rehabilitation settings. Static stretching (SS) has been used to increase the flexibility of muscles and reduce muscle stiffness, but the effects of SS on the stiffness of specific regions of the knee extensor mechanism are unclear. The quadriceps femoris and patellar tendon are essential components of the knee extensor mechanism and play an important role in knee motion. Therefore, we explored the acute and prolonged effects of SS on the stiffness of the quadriceps femoris and patellar tendon and knee flexion range of motion (ROM). Thirty healthy male subjects participated in the study. Three 60-second SS with 30-second intervals were conducted in right knee flexion with 30° hip extension. We measured the ROM and stiffness of the vastus medialis (VM), vastus lateralis (VL), and rectus femoris (RF) and the proximal-(PPT), middle-(MPT), and distal-(DPT) regions stiffness of patellar tendon before and immediately after SS intervention, or 5 and 10 minutes after SS. Stiffness of the quadriceps muscle and patellar tendon were measured using MyotonPRO, and the knee flexion ROM was evaluated using a medical goniometer. Our outcomes showed that the ROM was increased after SS intervention in all-time conditions (P＜0.01). Additionally, the results showed that the stiffness of RF (P < 0.01) and PPT (P = 0.03) were decreased immediately after SS intervention. These results suggested that SS intervention could be useful to increase knee flexion ROM and temporarily reduce the stiffness of specific regions of the knee extensor mechanism.